Retinal angiopathy and chronic arterial hypertension during pregnancy - Deinichenko, O. V.; Mladonov, V.; Mladonov, V.; Turchynenko, Yu.; Moskovka, V.; Bilan, I.; Дейніченко, Олена Валеріївна (My University, 2022)
Intensive care unit Central District Hospital Tomakivka, Dnipropetrovsk region, Ukraine Arterial hypertension in pregnant women is a concept that combines various forms of increasing blood pressure. Chronic hypertension (high blood pressure is detected even before pregnancy or for the first time - before the 20th week of pregnancy) occupies a special place among the pressing issues of modern medicine, especially in pregnant women.
Keywords: тези доповідей